2017
DOI: 10.1002/ptr.5810
|View full text |Cite|
|
Sign up to set email alerts
|

Auraptene Induces Apoptosis via Myeloid Cell Leukemia 1-Mediated Activation of Caspases in PC3 and DU145 Prostate Cancer Cells

Abstract: Although auraptene, a prenyloxy coumarin from Citrus species, was known to have anti-oxidant, anti-bacterial, antiinflammatory, and anti-tumor activities, the underlying anti-tumor mechanism of auraptene in prostate cancers is not fully understood to date. Thus, in the present study, we have investigated the anti-tumor mechanism of auraptene mainly in PC3 and DU145 prostate cancer cells, because auraptene suppressed the viability of androgen-independent PC3 and DU145 prostate cancer cells better than androgen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Specifically, coumarins' anti‐tumor responses are related to various mechanisms such as apoptosis induction, inhibition of cell growth, and of DNA‐associated enzymes, as topoisomerase (Majumdar et al, ). Characteristic examples of natural coumarins possessing anticancer effects are auraptene (Hasan, Genovese, Fiorito, Epifano, & Witt‐Enderby, ; Lee et al, ), umbelliprenin (Kavetsou et al, ), and umbelliferone (Mazimba, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, coumarins' anti‐tumor responses are related to various mechanisms such as apoptosis induction, inhibition of cell growth, and of DNA‐associated enzymes, as topoisomerase (Majumdar et al, ). Characteristic examples of natural coumarins possessing anticancer effects are auraptene (Hasan, Genovese, Fiorito, Epifano, & Witt‐Enderby, ; Lee et al, ), umbelliprenin (Kavetsou et al, ), and umbelliferone (Mazimba, ).…”
Section: Introductionmentioning
confidence: 99%
“…It also suppressed the expression of anti‐apoptotic proteins including Bcl‐2 and myeloid cell leukemia 1 (Mcl‐1) in these prostate cancer cells. The possible mechanism of chemo‐preventive effects of auraptene could be related to Mcl‐1‐mediated activation of caspases …”
Section: Resultsmentioning
confidence: 99%
“…The possible mechanism of chemo-preventive effects of auraptene could be related to Mcl-1-mediated activation of caspases. 38 The effect of auraptene was investigated on human renal cancer cells (RCC4 and RCC4/VHL cell lines). Results indicated that auraptene inhibited glycolytic and mitochondrial metabolism as well as VEGF and tube formation by HUVECs.…”
Section: Auraptene and Cancermentioning
confidence: 99%
“…Similar to current results, many studies have indicated delay in G 1 phase of the cell cycle upon X‐ray exposure, for instance in human glioma, leukemia, and holangiocarcinoma cells (Li et al, ; Wu et al, ; Hemaltulin et al, ). It has also been reported that auraptene, in toxic concentrations, induced sub‐G 1 peak in the flow cytometry histogram of breast, gastric, and prostate cancer cells (Mousavi et al, ; Moon et al, ; Lee et al, ) and inhibited cell proliferation by down regulating several genes involved in cell cycle control such as cyclin D1 , E2F1 , CDC2, and UHRF1, which promote G 1 to S phase transition (Krishnan and Kleiner‐Hancock, ). Accordingly, observed synergy between auraptene and radiotherapy in our study, which was confirmed by a sub‐G 1 peak on DNA content histogram of HT29 cells, might be resulted from the changed expression of cell cycle regulators mentioned earlier.…”
Section: Discussionmentioning
confidence: 98%
“…The outstanding finding was that auraptene pretreatment of cells induced more significant ( p < 0.01) increase in the expression of p21 after radiotherapy. This not only explains, to some extent, the detection of sub‐G 1 peak in flow cytometry histogram of auraptene pretreated cells after radiotherapy, also is in consistence with studies that reported auraptene inducing effects on cell cycle key inhibitors including BAX , p21 , P53 , DDIT3, and BCL2 (Mousavi et al, ; Saboor‐Maleki et al, ; Moon et al, ; Krishnan and Kleiner‐Hancock, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%